APLIKASI PENGENALAN SITUS BERSEJARAH DI KOTA PEKANBARU DENGAN AUGMENTED REALITY MARKERLESS BERBASIS ANDROID - Harun Mukhtar; Soni Soni; Heri Setiawan (JURNAL FASILKOM, 2019)
Historical sites are places or areas where there is information about historical relics. But ingeneral there are not many people who know the historical sites in Indonesia, especially in the city ofPekanbaru. The lack of information media also lies behind the public's ignorance. Therefore we needmedia publications to introduce these historic sites, namely by using Android-based Augmented RealityMarkerless technology. Making this application uses Blender software to create 3D objects andUnity3D software to create Augmented Reality applications. The purpose of this study is to help thepublic get to know the historical sites in the city of Pekanbaru by building interactive introductionmedia that can display photos and 3D objects from the site, it is hoped that people can more easilyrecognize and learn about historical sites in the city of Pekanbaru